2023
DOI: 10.1249/jsr.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is the Most Important Medicine for COVID-19

Georgia Torres,
Demitri Constantinou,
Philippe Gradidge
et al.

Abstract: COVID-19 infection and long COVID affect multiple organ systems, including the respiratory, cardiovascular, renal, digestive, neuroendocrine, musculoskeletal systems, and sensory organs. Exerkines, released during exercise, have a potent crosstalk effect between multiple body systems. This review describes the evidence of how exerkines can mitigate the effects of COVID-19 in each organ system that the virus affects. The evidence presented in the review suggests that exercise should be considered a first-line s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…At this moment, the exercise interventions of the rehabilitation programs prescribed for post-COVID-19 patients lacked detailed description of each exercise and how the starting levels and adherence to the programmers were assessed (Torres;Philippe, 2023). Other studies showed that resistance muscle training promotes physiological and structural changes in muscle fibers, such as an increase in the cross-sectional area of the muscle and a change from type I muscle fibers to type 2a muscle fibers (Mills et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this moment, the exercise interventions of the rehabilitation programs prescribed for post-COVID-19 patients lacked detailed description of each exercise and how the starting levels and adherence to the programmers were assessed (Torres;Philippe, 2023). Other studies showed that resistance muscle training promotes physiological and structural changes in muscle fibers, such as an increase in the cross-sectional area of the muscle and a change from type I muscle fibers to type 2a muscle fibers (Mills et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of the respiratory muscle is one of the main factors that increases exercise tolerance and promotes the improvement of lung function in COVID-19 patients, more specifically by increasing the strength of respiratory muscles, lung ventilation ability, as well as oxygen and alveoli combination (Bo;Xi;Tian, 2021). Different field tests have been studied to evaluate the exercise capacity of post-COVID19 patients and the response to physical rehabilitation programs (Del Valle et al, 2023;Visca et al, 2023;Torres;Philippe, 2023;Núñez-Cortés et al, 2022;Nopp et al, 2022;Peroy-Badal et al, 2022). We chose the 6MST because it is a stress test of easy application and low cost, easily performed in small spaces.…”
Section: Discussionmentioning
confidence: 99%